Production of biochar from microwave pyrolysis of empty fruit bunch in an alumina susceptor - Md Said, Mohamad Syazarudin; Azni, Atiyyah Ameenah; Wan Ab Karim Ghani, Wan Azlina; Idris, Azni; Ja'afar, Mohamad Fakri Zaky; Mohd Salleh, Mohamad Amran (ICE Publishing, 2021)
Biomass-derived biochar emerges as a potential green bio-coal candidate for power generation. Microwave-assisted pyrolysis has been proven to be an efficient and economical technique for biomass conversion into biochar. The process can be further improved by utilising susceptor. This research focuses on producing biochar from microwave pyrolysis of empty fruit bunch (EFB) in an alumina susceptor. EFB pellet (PEFB) and EFB short fibre (FEFB) were pyrolysed in a 14 L bench scale microwave pyrolyser at temperatures between 200 and 400 °C. The pyrolyser performance (biochar yield, energy efficiency) and biochar properties (proximate analyses, ultimate analyses, calorific value and ash content) were analysed. The results showed that temperature of 300 °C demonstrated the optimised conditions for biochar production. FEFB produced 5.2% higher biochar yield and exhibited better biochar properties compared to PEFB. FEFB-derived biochar (FEFBC) overall characteristics were better than PEFB-derived biochar (PEFBC), with higher heating value (25.19 MJ/kg), fixed carbon (64.52%), volatile matter (13.38%) and carbon content (59.83%). However, FEFBC has high tendency of forming slagging and fouling in the combustor as the ash indexes were > 0.34 kg/GJ and RB/A > 1.75.